Prevalencia de Parásitos Gastrointestinales en Gatos Domésticos (felis catus) en la Parroquia La Matriz del Cantón Latacunga. - Briones Silva, Kevin Isaac (2019)
This research is about " Gastrointestinal Parasites Prevalence in domestic cats (Felis Catus) at La Matriz parish of Latacunga city." Determining gastrointestinal parasites by The Faust flotation technique, establishing if the positive and negative cases are related to age and sex and determining the currently parasites to socialize the results with their owners, were the main objective of this research. This research was carried out at La Matriz parish; 100 cats were sampled in four neighborhoods, taking 25 samples from each sector, analyzing in two research groups (Sex and Age). About obtained results, 71% cats tested positive for gastrointestinal parasites, which (37 females) 67.27% and (34 males) 75.56%. Isospora spp was the most frequent parasite with 54.0% in females and 58.82% in males. According to the age group, was determined (19 less to 6 months) 70.37% and (52 older than 6 months) 71.23% positive in the presence of gastrointestinal parasites. Isospora spp was the most frequent parasite in older cats than 6 months with 78.85% and in younger cats than 6 months, Toxocara cati with 73.68%.